Pelabelan Negatif terhadap Ekspresi Feminin pada Laki-laki: Analisis Stigma 'Boti' dalam Interaksi Sehari-hari di Media Sosial dan Ruang Publik Indonesia - Elisabet Claudya Septiani Silaban; Salwa Zahira; Ika Arinia Indriyany (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study examines the negative labeling of feminine expression among men in Indonesia through the stigma associated with the term “boti” within everyday interactions in social media and public spaces. The research employs an empirical qualitative socio-legal approach combining phenomenology and critical discourse analysis to explore how stigma is produced, circulated, and normalized within digital and social environments. Data were collected through social media content analysis on platforms such as Twitter/X, Instagram, and TikTok, alongside semi-structured interviews involving informants selected through purposive sampling. The findings reveal that the use of the term “boti” functions not merely as colloquial slang but as a symbolic instrument that reinforces hegemonic masculinity, regulates gender expression, and reproduces hierarchical gender norms in Indonesian society. From a socio-legal perspective, the persistence of such stigma highlights tensions between constitutional guarantees of expression and the protection of personal dignity under Indonesian law. Strengthening inclusive digital governance and gender-sensitive legal interpretation is therefore essential to prevent symbolic discrimination in contemporary public discourse.